Oxidation of aqueous humic substances by ozonation - Kerç, Aslıhan. (Thesis (Ph.D) - Bogazici University. Institute of Environmental Sciences, 2002., 2002)
Chemical oxidation techniques have been used in water treatment for the removal of natural organic matter, which produce halogenated organic compounds upon chlorination. Although being a powerful oxidant, ozone is known to be ineffective for oxidizing recalcitrant organics. Accumulation of carboxylic acids upon ozonation makes the complete mineralization impossible or unfeasible. Therefore, in this study ozonation was combined with photocatalytic oxidation using TiO2 for humic acid degradation. First part of this study covers the ozonation kinetics in humic acid solutions. An empirical model was proposed for defining humic acid degradation with ozonation. The proceeding sections cover the combination of ozonation with photocatalytic oxidation in a sequential system in which ozonation was applied as a pretreatment stage. Langmuir-Hinshelwood model as well as first order degradation kinetics model was studied for defining the photocatalytic oxidation of humic acids. Pretreatment by ozonation resulted in increased first order degradation rates during photocatalysis. Adsorption characteristics of humic acids on the catalyst surface were also evaluated. UV absorbance and color were the parameters used to monitor humic acid degradation. The changes in the molecular size distributions were determined in oxidized humic acid samples using ultrafiltration. Trihalomethane formation potential (THMFP) was measured to demonstrate the oxidation efficiencies.
Keywords: Humic acid.; Water -- Purification -- Photocatalysis.; Water -- Purification -- Ozonization.